THE IMPLEMENTATION OF SMALL GROUP DISCUSSION TECHNIQUE IN TEACHING READING ANALYTICAL EXPOSITION TEXT (RETAIN, 2013)
Classroom reading activities are essential is EFL learning. In reading, there is a process of receiving knowledge and information. As a receptive skill, reading is meant to prepare the learners with sufficient information before proceeding to the production of the language. However, reading is often considered as a passive activity. Many teachers nowadays put the focus on the production of the language which, in their opinion, truly shows the success of the learning process. In this qualitative study, the researcher observes a teacher implementing Small Group Discussion in teaching reading analytical exposition text. This teaching technique allows the students to work in small groups, exchange ideas, and learn from the others in the same group. The result shows that the teacher did not fully follow the theories given by experts. However, the teacher manages to successfully implement the teaching technique. Also, the students have positive responses on the implementation of Small Group Discussion. Small Group Discussion is not limited to be implemented only for reading activities. Individually or integrated, this teaching technique can be implemented to any language skill in any language classroom activity. The implementation will be considered successful if it matches with the material and meets the students’ needs. Keywords: Small Group Discussion, Teaching Reading, Analytical Exposition